Dyslipidemia in Psoriasis: A Case - Controlled Study - Monique Kafle; Madhu Gyawlee; Amit Amatya; Bhaskar Mohan Meher Kayastha; Smarika Upadhyaya (Nepal Journal of Dermatology, Venereology & Leprology)
INTRODUCTION:  Psoriasis is a chronic inflammatory condition of skin which can be associated with other ailments including dyslipidemia which is an abnormal serum lipid profile.